Evaluation of the Feedback on the Attitude, Ethics, and Communication Module by First-Year Faculty Members in Medical Colleges - Rekha Udgiri; Praveen Ganganahalli (Strides in Development of Medical Education)
Background: The National Medical Commission (NMC) of India has prepared a revised graduate medical training program for Indian medical graduates to develop the requisite knowledge, skills, attitude, values, and responsiveness as physicians of the first contact with the community. The attitude, ethics, and communication (AETCOM) module has been prepared as a guide to facilitate implementing a longitudinal program for institutions and faculty members that will help the students acquire the essential competency domains. The present study was an attempt to know the faculty members’ perception regarding the AETCOM module based on analyzing and addressing the suggestive measures.Objectives: To know the faculty perception regarding AETCOM module & based on the analysis, suggestive measures are recommendedMethods: The present research was a cross-sectional study. The data were collected using semi-structured questionnaires. Those who submitted the responses were included in the study. The feedback form, along with the AETCOM module curriculum, was e-mailed to those who have undergone one or the other faculty development training program from different colleges of the first professional year faculties. A total of 34 faculty members out of 60 participated in the study.Results: About 65% of the participants were females, 50% were professors, and 44% belonged to private and deemed university colleges, respectively. The majority (60%) of the participants were told to reduce the duration of modules and avoid the repetitions concerning the communication skill modules.Conclusion: According to the study findings, we conclude that the implementation of the AETCOM module is a good initiative taken by the NMC. The competencies specified within each module underscore the importance of cultivating attitudes, ethics, and communication skills among Indian medical graduates, reflecting the contemporary demands and standards of the healthcare profession.